ANALISIS MARJIN PEMASARAN PENGECER AYAM POTONG DI PD PASAR JAYA PASAR MINGGU - Oki Oktavia Putri; . Yodfiatfinda (JURNAL BIOINDUSTRI (JOURNAL OF BIOINDUSTRY), 2021)
This research was about broiler chicken business in PD Pasar Jaya, Pasar Minggu, Jakarta Selatan by focussed on its market margin. The research objective was to identify marketing channels for broiler chicken, analyze the marketing margins of broiler retailers, and providing recommendation for broiler marketing channel management. The analysis method used was descriptive, marketing marjin, and marketing efficiency. There were four patterns of marketing channels and five marketing agencies. The most efficient marketing channel for broiler chickens was Channel 1 in the domestic chickens. Farmers distribute it directly to the retailers. Channel 1 had the lowest marketing marjin of IDR 16,000. The highest farmer's share value was 78%, meaning that the farmers received 78% of the price paid by the consumer. Marketing cost in the channel 1 was the smallest amounting to Rp 943. Marketing channel was efficient if the value was less than 5%, therefore channel 1 was the most efficient due to the value is the lowest at 1%. Chicken price fluctuations influenced by supply-demand which was subject to particular moments. An effective management recommendation define an effective and efficient marketing channel to set margins on the raw product so that the fair distribution of the margins between marketing channels. The fluctuation of chicken prices in breeders can be overcome by determining the period of raising chickens according to the demand data during particular moment.